ISLAM NUSANTARA: ANALISIS KONSEP PEMIKIRAN WASATHIYAH DAN FONDASI MODERASI ISLAM DI INDONESIA - Nurul Mustofa; Purna Wirawan; Sumiati; Hidayatuz Zainiyah (Pascasarjana Universitas Al-Qolam Malang, 2026)
Religious moderation in the perspective of Islamic archipelago is a concrete manifestation of the concept of wasathiyah (middle way) in Islam. This concept represents moderate Islamic thought that prioritizes the values of tawassuth, tawazun, I'tidal, and tasammuh as a tolerant and harmonious religious style and becomes the foundation in building moderation practices in Indonesia. This research aims to analyze the concept of wasathiyah (moderate) thought in Islam Nusantara and how these ideas contribute to the formation of Islamic moderation in Indonesia. This research uses a qualitative approach with a literature study method. The results of the study show that Islam Nusantara as the concept of wasathiyah thinking has a major role in fostering religious moderation in Indonesia. Islam Nusantara is able to answer the challenges of the times such as Radicalism and Intolerance. This research is expected to make an academic contribution to strengthen moderate Islamic discourse and become a reference in efforts to maintain religious harmony and strengthen social integration in the midst of diversity.